2017
DOI: 10.1016/j.healthplace.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Place and recovery from alcohol dependence: A journey through photovoice

Abstract: It has been suggested that place, and interaction with the environment, may play a role in recovery from alcohol dependence. In this paper we report findings from a project that used an adapted photovoice methodology to better understand individuals' experience and perceptions of the role of place in recovery from alcohol dependence. Individuals attending a recovery café in central Scotland documented their environment and, in focus group settings, the individuals discussed and analysed their photographs. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…With these points in my mind, we see Health & Place continuing as a key outlet for place-related research on physical activity, diet and food, and other health-related behaviours, notably smoking and drinking. Recent examples include Chambers et al (2017), Moon et al (2018), Shortt et al (2017), Macdonald et al (2018), and (Mooney et al, 2018). We also see a continuing key role for research on environments and health (eg.…”
Section: Discussionmentioning
confidence: 99%
“…With these points in my mind, we see Health & Place continuing as a key outlet for place-related research on physical activity, diet and food, and other health-related behaviours, notably smoking and drinking. Recent examples include Chambers et al (2017), Moon et al (2018), Shortt et al (2017), Macdonald et al (2018), and (Mooney et al, 2018). We also see a continuing key role for research on environments and health (eg.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors emphasise the fundamentally therapeutic qualities of natural elements (Day,2007;Finlay et al 2015;Grose, 2011;Serbulea & Payyappallimana, 2012;Thomas, 2015;Volker and Kistemann, 2015;Wang et al 2018;Windhorst & Williams, 2015). Others, however, stress the therapeutic valences of non-natural elements (e.g., Bornoli et al, 2018;Masuda and Crabtree, 2010;Piet et al,2017;Shortt et al,2017). More recently, authors have picked up on ideas posited by Volker and Kistemann ( 2015) that seek to take a more subtle approach to understanding the salutogenetic and therapeutic relationships between people and different types of natural landscapes.…”
Section: Spaces Of Carementioning
confidence: 99%
“…However, other methodologies such as Participatory Action Research (PAR) might show results that are difficult to be revealed by other methodologies [33]. One such approach is Photovoice, which involves the participants in a critical discussion about a specific issue through the use of photography [34][35][36][37]. This methodology had been used previously among people with alcoholic problems [37].…”
Section: Introductionmentioning
confidence: 99%
“…One such approach is Photovoice, which involves the participants in a critical discussion about a specific issue through the use of photography [34][35][36][37]. This methodology had been used previously among people with alcoholic problems [37]. Participants identified that high exposure to alcohol availability and promotion were hindering their recovery.…”
Section: Introductionmentioning
confidence: 99%